الإدارة البيئية وآليــــــــــــــات تــــفعيلهـــــــــــا في الـمؤسسـة الصحيــــة - بوقرة, رابح (جامعة مسيلة, 2018)
The relationship between health, environment and sustainable development has three main components. First, the protection of human health and its environment contributes to sustainable development and poverty reduction; second, health can be one of the main outcomes of investment in sustainable development and the green economy; To measure progress socially, economically and environmentally towards sustainable development. The increase in interest in the environment and its preservation in the context of sustainable development impose this reality on organizations of all kinds to adopt environmental management systems. The latter works through effective mechanisms to reduce the damage caused by the activities of these organizations to the environment. As a result of the tremendous scientific progress in the field of Its colors and forms were necessary for health organizations like other organizations have modern management commensurate with the data of the age, and take into account all the standards and dimensions of health service, starting from the inputs tell the output, and the outputs of health organizations provided to the health service Which are in themselves hazardous to public health and the environment, particularly hazardous health-care waste. All wastes that have natural, chemical or biological properties require special handling and disposal methods to avoid their risks to public health and the environment. It is necessary to have safe and reliable ways to handle these wastes where they are generated. Hospitals and health care organizations have a duty to care for the environment and public health and have special responsibilities with respect to their waste to ensure that there are no adverse health and environmental consequences. Through the adoption of the environmental management system at various stages of providing health care services. Therefore, through this study we will try to highlight the most important mechanisms of environmental management that the health institution uses as a service sector to reduce the environmental damage resulting from various activities of waste
Keywords: environmental management, environmental performance, health institution, waste health care services, sustainable development. Jel Classification Codes: M1,Q53,I1